Investigating the relationship between academic procrastination, internet addiction, and academic performance among Medical Sciences students, Birjand, Iran - Abbas Javdi; Yahya Mohammadi (Future of Medical Education Journal)
Background: The primary goal of universities is to educate and train students. However, one significant challenge students face today, which negatively impacts their learning and academic success, is academic procrastination and internet addiction. Therefore, this study was explored the relationship between academic procrastination, internet addiction, and academic performance among students at Birjand University of Medical Sciences.Method: This correlational study included all students of Birjand University of Medical Sciences in the academic year 2024-2025. The sample size was estimated to be 305 people based on the Krejcie and Morgan table. Solomon's Academic Procrastination Scale (1984), Kimberly Young's Internet Addiction Scale (1988), and Dartaj's Academic Performance Scale (2004) were used to collect data. Data analysis was performed using SPSS 22 software and Pearson correlation coefficient, one-sample t-test, independent samples t-test, and analysis of variance (ANOVA) at a significance level of 0.05.Results: There was a significant positive relationship between student academic procrastination and internet addiction (r=0.35, p<0.0001), and it can be said that 12% of students' academic procrastination can be predicted by internet addiction. Students' academic performance was negatively impacted by academic procrastination (r=-0.42, p<0.0001).Conclusion: Internet addiction and academic procrastination are inversely related to academic performance. This suggests that managing both internet addiction and procrastination among students can lead to improved learning outcomes.